Multiple antibiotics resistant among environmental isolates of Stenotrophomonas maltophilia - E O Igbinosa; F E Oviasogie (Journal of Applied Sciences and Environmental Management, 2014)
In this study we assessed the functionality of integrons, melanin-like pigment and biofilm formation on multidrug resistance among environmental isolates of Stenotrophomonas maltophilia. Marked resistances were noted against aztreonam (60%), cefepime (68%), ceftazidime (77%), ciprofloxacin (72%), gentamicin (65%), meropenem (75%), piperacillin/tazobactam (65%) in S. maltophilia. Ticarcillin/clavulanic acid (66%) and trimethoprim/sulfamethoxazole (75%) were the active antibiotics against S. maltophilia. Class 1 intergron was significantly detected in 56.3% (54/96) of S. maltophilia strains. Integron-positive strains were significantly resistant to cefepime (69%), ceftazidime (78%), ciprofloxacin (74%), gentamicin (65%), and meropenem (72%). Gene cassettes arrays within integrons were identified as aminoglycoside resistance genes aacA4, aadA2, aadB, aacC4, and aacA6'-Ib; β- lactams resistance genes blaIMP, blaOXA, and blaCARB; chloramphenicol resistance genes cmlA and catB2; quaternary ammonium compound (QAC) resistance genes smr and qac; and multi-gene cassettes: smr/aacA4 and blaIMP/aac6-II/aadA5. High-pigment-producing S. maltophilia strains revealed significant correlation with resistance to cefepime, ceftazidime, ciprofloxacin, levofloxacin and piperacillin/ tazobactam. Biofilm formation was not significant with resistance to ciprofloxacin, levofloxacin, meropenem, ticarcillin/clavulanic and trimethoprim /sulfamethoxazole. Our findings characterize the significant roles of integrons, melanin-like pigment and biofilm formation in the multidrug resistance of S. maltophilia. The range of antibiotics resistance genes and mobile genetic elements found suggests that the organism could potentially act as a reservoir of drug resistance determinants in environmental and clinical settings, which is an issue of public health concern.